AI-Driven Learning Environments and Learning Flow Experience: The Role of Technological Readiness in Supporting Sustainable Quality Education - Ani Nurhayati; Ulfia Rahmi; Abna Hidayati; Septriyan Anugrah; Indra Saputra (Postgraduate, University of Mataram, 2026)
This study examines the determinants of learning flow experience in AI-driven learning environments and its contribution to Sustainable Development Goal 4 (Quality Education). A quantitative approach was employed using survey data from 316 undergraduate students experienced in AI-integrated courses across four faculties at Universitas Negeri Padang, Indonesia. The data were analyzed using partial least squares structural equation modeling (SEM-PLS). The results indicate that AI technological readiness has a significant positive effect on learning flow experience and mediates the influence of instructor support, community support, and teaching platform quality on learning flow. In contrast, AI digital literacy does not have a significant effect on technological readiness, indicating that technical training alone is insufficient and cannot independently build learners’ readiness without strong pedagogical and contextual support. Furthermore, AI facilitating conditions slightly but significantly strengthen the relationship between technological readiness and learning flow, suggesting their role as a contextual boundary factor. These findings highlight the importance of integrating instructional, technological, and institutional support systems in AI-driven learning. In conclusion, fostering technological readiness through supportive learning ecosystems is essential for promoting meaningful and sustainable learning experiences aligned with SDG 4.